Antibody to a human DNA repair protein allows for cloning of a Drosophila cDNA that encodes an apurinic endonuclease. - Kelley, M R (1989)
The cDNA of a Drosophila DNA repair gene, AP3, was cloned by screening an embryonic lambda gt11 expression library with an antibody that was originally prepared against a purified human apurinic-apyrimidinic (AP) endonuclease. The 1.2-kilobase (kb) AP3 cDNA mapped to a region on the third chromosome where a number of mutagen-sensitive alleles were located. The cDNA clone yielded an in vitro translation product of 35,000 daltons, in agreement with the predicted size of the translation product of the only open reading frame of AP3, and identical to the molecular size of an AP endonuclease activity recovered following sodium dodecyl sulfate-polyacrylamide gel electrophoresis of Drosophila extracts. The C-terminal portion of the predicted protein contained regions of presumptive DNA-binding domains, while the DNA sequence at the amino end of AP3 showed similarity to the Escherichia coli recA gene. AP3 is expressed as an abundant 1.3-kb mRNA that is detected throughout the life cycle of Drosophila melanogaster. Another 3.5-kb mRNA also hybridized to the AP3 cDNA, but this species was restricted to the early stages of development.